Pengaruh Disiplin, Motivasi, dan Pelatihan Terhadap Kinerja Guru di SMP Negeri 3 Jepon Blora Tahun 2020 - Pardi . (JI@P, 2022)
The background of this study is Law Number 5 of 2014 about ASN. And then teacherperformance at the school has not maximized related to discipline, motivation, andtraining. The study is aimed to determine and analyze simultaneous influence ofdiscipline, motivation, and training on the teacher performance at SMP Negeri 3Jepon Blora in 2020. This study was a quantitative research. The sample consistsof 20 teachers. The data analysis technique used was multiple linear regressionswith F test and t test. While data processing using the SPSS method. Conclussionsin this study showed that there are a simultaneously significant influence ofdiscipline, motivation, and training on teacher performance at SMP Negeri 3 JeponBlora in 2020.Keywords: Discipline, Motivation, Training, Teacher Performance.